1972
DOI: 10.1002/anie.197205441
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Detection of Vinyl Cations

Abstract: Vinyl cations ( I ) , unknown and rejected a few years ago, are now the subject of an increasing number of investigations. In these cations the formal positive charge resides on the carbon atom of an olefinic double bond. With twopresumably linearly-attached ligands they belong to the group of disubstituted carbenium ions.The objections which have frequently been raised against the existence of vinyl cations are justifiable inasmuch as simple vinyl halides ( 2 ) @=halogen) resist hydrolysis and do not precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Studies with model compounds revealed that phenolic b-aryl-ether (b-O-4) structures react with anthrahydroquinone (AHQ) -via quinone-methide intermediate to give adducts which are susceptible to fragmentation in alkaline solution (Aminoff et al 1979;Gierer et al 1979;Landucci 1980). The resulting adducts then undergo a Grob-type heterolytic fragmentation (Grob and Schiess 1967;Grob 1969Grob , 1972 of b-aryl-ether bond with concomitant regeneration of AQ ( Figure 1) (Gierer et al 1979;Landucci 1980). In addition to this type of reductive cleavage, it was suggested that oxidation of g-CH 2 OH end-groups in lignin side chains by AQ to corresponding g-CHO end-groups occurs (Araki et al 1979;Schroeter 1980;Hise et al 1983Hise et al , 1987 (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with model compounds revealed that phenolic b-aryl-ether (b-O-4) structures react with anthrahydroquinone (AHQ) -via quinone-methide intermediate to give adducts which are susceptible to fragmentation in alkaline solution (Aminoff et al 1979;Gierer et al 1979;Landucci 1980). The resulting adducts then undergo a Grob-type heterolytic fragmentation (Grob and Schiess 1967;Grob 1969Grob , 1972 of b-aryl-ether bond with concomitant regeneration of AQ ( Figure 1) (Gierer et al 1979;Landucci 1980). In addition to this type of reductive cleavage, it was suggested that oxidation of g-CH 2 OH end-groups in lignin side chains by AQ to corresponding g-CHO end-groups occurs (Araki et al 1979;Schroeter 1980;Hise et al 1983Hise et al , 1987 (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…If, R =ethoxycarbonylmethyl A yellow oil; IR (neat) 1790, 1750, 1640 cm'. lH NMR (CDCl;) 8 1.24 (3R, t, J :::7 Hz, OCH 2 CH 3 ) , 1.33 (3H, t, J::: 7 Hz, OCH£H3) , 2.06 (3H, S, OqO)CH 3 ) ,3.77 (2H, S, (O)CCH2C(O», 4.16 (2H, q, J =7 Hz, OCHzCH3), 4.34 (2H, q, J '" 7 Hz, OCH2C H 3 ) . MS (12 eV) m/z 231 (M+ • CHz=C=O, 20), 185 (l00), 157 (35).…”
mentioning
confidence: 99%